Pemanfaatan Sumber Belajar dalam Bidang Bimbingan dan Konseling - Purbatua Manurung (Sekolah Tinggi Agama Islam Sumatera Medan, 2020)
This study aims to analyze the use of learning resources in the field of counseling guidance. This study uses a qualitative research method based on library research (library research). Collecting data using documentation techniques derived from library sources. Data analysis uses content analysis techniques where each source or literature used is adjusted and the context's suitability is seen with other literature from books, journals or other research. At present the quality of learning and community education is strongly influenced by the conditions of existing learning resources, and this cannot be denied because if the conditions and availability of learning resources are adequate, the learning process can run well. This indirectly shows how important it is to use learning resources in a learning process. In the realm of guidance and counseling, learning resources are closely related and are often used in various implementation of guidance and counseling services, both in the formal and non-formal world of education, in this case the associated learning resources can be in the form of religion or instruments used in the successful implementation of guidance and counseling service.